Fuel Properties and Emissions of Soybean Oil Esters as Diesel Fuel - Chang, D.Y.Z.; Van Gerpen, I.H.; Lee, I.; Johnson, L.A.; Hammond, E.G.; Marley, S.J.
The effects of using blends of methyl and isopropyl esters of soybean oil with No. 2 diesel fuel were studied at several steady-state operating conditions in a four-cylinder turbocharged diesel engine. Fuel blends that contained 20, 50, and 70
Keywords: BIODIESEL; DIESEL ENGINE; ENGINE EMISSIONS; ENGINE PERFORMANCE; FUEL PROPERTIES; ISOPROPYL ESTER; METHYL SOYATE; PARTICULATE EMISSIONS; WINTERIZATION